2019
DOI: 10.1126/scitranslmed.aaw2127
|View full text |Cite
|
Sign up to set email alerts
|

Driving CAR T cell translation forward

Abstract: Successes in CAR T cell translation have propelled their commercial launch, but expanding the impact of cancer immunotherapies remains challenging.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
63
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 66 publications
(70 citation statements)
references
References 10 publications
0
63
0
Order By: Relevance
“…Of all the tested constructs, CAR that incorporated the TM region of CD28 performed optimally (Figure 2). This strengthens the need to examine CAR function empirically 19,36‐38 . Closer examination of the critical Ig‐domains in the extracellular siglec‐7 moiety showed that the main functional domains for tumor recognition were 1 and 3.…”
Section: Discussionmentioning
confidence: 76%
“…Of all the tested constructs, CAR that incorporated the TM region of CD28 performed optimally (Figure 2). This strengthens the need to examine CAR function empirically 19,36‐38 . Closer examination of the critical Ig‐domains in the extracellular siglec‐7 moiety showed that the main functional domains for tumor recognition were 1 and 3.…”
Section: Discussionmentioning
confidence: 76%
“…Owing to emergence of relapse of ALL with cells that do not express CD19 in mechanisms of a phenomenon known as antigen escape, the Phase I study with the use of CAR-T cells with dual targeting of CD19/CD22 has demonstrated good efficacy, safety, and tolerability, thus opening possibility to trials studying bispecific targeting to circumvent CD19 down-regulation [17,23,24].…”
Section: Further Progress and Worldwide Distributionmentioning
confidence: 99%
“…52,53) Engineered CARs target many other antigens of blood cancers, including CD30 in Hodgkin's lymphoma as well as CD33, CD123, and FLT3 of acute myeloid leukemia. 54) Recent research has shown that Cas9-mediated PD-1 disruption in the CAR-T cells improved the anti-tumor effect observed in in-vitro and in-vivo experimental models, leading to the performance of a clinical trial. 55,56) All other ongoing clinical trials using genome-editing technologies are highlighted in Table 3.…”
Section: Applications Of Genome Editing Technologiesmentioning
confidence: 99%